1999
DOI: 10.1074/jbc.274.31.22048
|View full text |Cite
|
Sign up to set email alerts
|

Gi Protein-mediated Functional Compartmentalization of Cardiac β2-Adrenergic Signaling

Abstract: In contrast to ␤ 1 -adrenoreceptor (␤ 1 -AR) signaling, ␤ 2 -AR stimulation in cardiomyocytes augments L-type Ca 2؉ current in a cAMP-dependent protein kinase (PKA)-dependent manner but fails to phosphorylate phospholamban, indicating that the ␤ 2 -AR-induced cAMP/PKA signaling is highly localized. Here we show that inhibition of G i proteins with pertussis toxin (PTX) permits a full phospholamban phosphorylation and a de novo relaxant effect following ␤ 2 -AR stimulation, converting the localized ␤ 2 -AR sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
130
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 31 publications
(53 reference statements)
9
130
1
1
Order By: Relevance
“…Alternatively, other studies performed in rat, dog, and mouse hearts have suggested a dual coupling of ␤ 2 -AR to concurrent G s and PTX-sensitive G i signaling pathways (45)(46)(47). In those species, the ␤ 2 -AR/G i pathway seems to exert a negative control on the ␤ 2 -AR/G s pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, other studies performed in rat, dog, and mouse hearts have suggested a dual coupling of ␤ 2 -AR to concurrent G s and PTX-sensitive G i signaling pathways (45)(46)(47). In those species, the ␤ 2 -AR/G i pathway seems to exert a negative control on the ␤ 2 -AR/G s pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Fractionation studies show that ␤ 2 ARs are concentrated in caveolae structures, whereas ␤ 1 ARs are mainly distributed in non-caveolar membrane on the cardiac myocyte plasma membrane (9,10). Moreover, studies show that ␤ 2 AR signaling can modulate L-type Ca 2ϩ channel activity in distinct subcellular microdomains in hippocampal neurons and cardiac myocytes (11)(12)(13). These observations suggest that distinct signaling complexes may exist in cardiac myocytes to conduct ␤ 1 and ␤ 2 AR signaling.…”
mentioning
confidence: 92%
“…β 1 ARs and β 2 ARs signal through Gα s and AC with similar efficacy. However, the signals are compartmentalized differently in cardiomyocytes, possibly due to their localization in distinct membrane microdomains and/or dual coupling of the β 2 AR to Gα s and Gα i [3]. β 2 ARs also have a high level of spontaneous activity not detected for β 1 AR [4].…”
Section: Introductionmentioning
confidence: 99%